2012
DOI: 10.1590/s0366-69132012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization of archaeological pot sherds recently excavated in Nedunkur, Tamilnadu, India

Abstract: The archaeological pottery sherds excavated recently in Nedunkur, Tamilnadu, were analysed using Thermogravimetric (TG) and Differential Thermal analysis (DTA) with an objective of identifying the mineralogical characteristics of the raw materials used for their production. Besides, the thermal reactions associated over the linear temperature ramp from room temperature to 1200 °C in an inert atmosphere were also realized by TG-DTA. The characterization studies were able to indicate the conditions of firing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Due to the presence of biotite in the XRD patterns of all ceramics, it can be assumed that those presenting brown/ red colour or a combination of brown and black colours on the cross section were fired below 1000 °C. In accordance with the DTA/TG results, the exothermic peak in the range of 850-1000 °C indicated that the samples were fired at 900 °C or even below this temperature [41]. For the sherds, which present black colour on the cross section (reducing atmosphere), the estimated firing temperature could be less than 750 °C.…”
Section: Estimation Of the Firing Conditionssupporting
confidence: 83%
See 1 more Smart Citation
“…Due to the presence of biotite in the XRD patterns of all ceramics, it can be assumed that those presenting brown/ red colour or a combination of brown and black colours on the cross section were fired below 1000 °C. In accordance with the DTA/TG results, the exothermic peak in the range of 850-1000 °C indicated that the samples were fired at 900 °C or even below this temperature [41]. For the sherds, which present black colour on the cross section (reducing atmosphere), the estimated firing temperature could be less than 750 °C.…”
Section: Estimation Of the Firing Conditionssupporting
confidence: 83%
“…A weak thermal effect at 573 °C corresponded to the allotropic transformation of quartz. A broad endothermic peak starting at around 620 °C accompanied by a loss of weight of 0.43% corresponded to the decomposition of carbonate, mainly calcite [28,[40][41][42]]. An exothermic peak starting at around 850 °C corresponded to the transformation of metakaolinite probably to gamma alumina or mullite according to the literature [32,43,44].…”
Section: Ceramicsmentioning
confidence: 95%
“…This possibility is substantially related to the firing technique used by the potters, and in this case, it seems like a kiln or at least a firing environment under control should be employed. Organic materials that would originate from the clay or would be subsequently added in order to increase the plasticity of the ceramic paste may also bring the black‐gray colors, but the coloring sequence on these samples (a red core between black‐gray surfaces) does not seem to be occurred thanks to such additives. Furthermore, for the sample of MW‐5, micro‐Raman analysis (Figure ) revealed the simultaneous presence of amorphous carbon with the band value of 1,601 cm −1 and hematite at 1,324 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…% for ET-3 and 9.51 wt. % for ET-5) at this temperature range [4,20,31]. The absence of enthalpy changes and ignorable mass loss (Table 6) after 900 o C implied that the sinterization behavior was limited, and thus the firing temperature likely did not exceed this range [4].…”
Section: Thermal Analysis (Tg-dta)mentioning
confidence: 99%